The Impact of Consumer Ethnocentrism, Perceived Quality, and Emotional Value on Purchase Intention of Local Brand Streetwear Products in Generation Z in Jakarta - Sherina Sherina; Frangky Selamat (International Journal of Application on Economics and Business, 2023)
This study was conducted to determine the effect of consumer ethnocentrism, perceived quality, and emotional value on the intention to buy streetwear products from Generation Z local brands in Jakarta. The sampling method used is non-probability sampling with convenience sampling technique. Data collection using a google form questionnaire distributed through social media with a number of respondents as many as 200 people but only 197 that can be analyzed further. The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SMARTPLS v3.2.9 statistical software. The sample in this study is Generation Z with an age range of 9-24 years who live in Jakarta who are familiar with local brand streetwear products. The results indicate that consumer ethnocentrism, perceived quality, and emotional value have a positive impact on the purchase intention of Generation Z to purchase local brand streetwear in Jakarta. For street wear fashion marketers, the results provide a better understanding of the increasingly dynamic consumer behavior of Generation Z.